Direct numerical simulation of a turbulent boundary layer with passive scalar transport - Li, Qiang; Schlatter, Philipp; Brandt, Luca; Henningson, Dan S. (ERCOFTAC Series, 2010)
A fully-resolved direct numerical simulation (DNS) of a spatially developing turbulent boundary layer with passive scalars over a flat plate under zero pressure gradient (ZPG) has been carried out using a spectral method with about 40M grid points. The highest Reynolds number based on the momentum thickness and free-stream velocity is Reθ = 850 and the molecular Prandtl numbers for the scalars range from 0.2 to 2.0. The intermittent region near the boundary-layer edge was identified by investigating the high-order moments and PDF. In addition, it was found that the streamwise velocity is similar to the scalar distribution at Pr = 0.71 with isoscalar wall boundary condition. Far away from the wall, the two quantities become less correlated.
CRIS-Team Scopus Importer:2023-03-21